Hadith #559 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Asim bin al-Mndhr bin al-Zubair عاصم بن المنذر بن الزبير بن العوام; Hammad bin Salama حماد بن سلمة; ibn Umar; Ubaidullah bin 'Abdullah bin 'Umar عبيد الله بن عبد الله بن عمر بن الخطاب; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“I asked Abu Sa’eed Al-Khudri about the prayer of the Messenger of Allah (ﷺ). He said: ‘There is nothing good in that for you.’* I said: ‘Explain it, may Allah have mercy on you.’ He said: ‘The Iqamah would be given for the Zuhr prayer for the Messenger of Allah (ﷺ), then one of us would go out to Al- Baqi’, relieve himself, then come back and perform ablution, and he would find the Messenger of Allah (ﷺ) still in the first Rak’ah of Zuhr.’”
Grade: